2021
DOI: 10.1007/s12564-021-09708-7
|View full text |Cite
|
Sign up to set email alerts
|

Perpetuating student inequality? The discrepancy and disparity of global citizenship education in Chinese rural & urban schools

Abstract: Global citizenship education (GCE) has been implemented in schools as an approach to address growing global issues and increase the internationalization of education. From critical discourse, however, the implementation of GCE seems to be thwarted by neoliberal practices that deepen societal inequality and gaps, and only benefit members of elite groups. This study aims to analyze teachers' perceptions and the school-based concrete implementation of context-specific GCE in China, unveiling not only the co-exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 54 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…However, notwithstanding the concept of global citizenship has been incorporated into Chinese government policy, there is still no specific definition of GCE from the relevant policy on the national curriculum (Li, 2021), nor any explanation of what GCE should look like and how it should be implemented in China. Moreover, since Han Chinese make up the vast majority of Chinese population, students may lack the opportunity to engage in consideration of complexities and realities of living in a multi-ethnic society (Mansilla & Wilson, 2020).…”
Section: Gce In China and National Identitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, notwithstanding the concept of global citizenship has been incorporated into Chinese government policy, there is still no specific definition of GCE from the relevant policy on the national curriculum (Li, 2021), nor any explanation of what GCE should look like and how it should be implemented in China. Moreover, since Han Chinese make up the vast majority of Chinese population, students may lack the opportunity to engage in consideration of complexities and realities of living in a multi-ethnic society (Mansilla & Wilson, 2020).…”
Section: Gce In China and National Identitymentioning
confidence: 99%
“…Since China's citizenship education is stateled, Chinese culture has always been an important part of China's citizenship education as well as a significant element of Chinese identity (Law, 2013). Moreover, Li (2021) carried out a case study to compare the implementation of GCE between Chinese rural and urban schools from teachers' perspectives, and the findings showed that teachers had a broad notion of GCE and disparities were identified between rural and urban schools. Woods and Kong (2020) explored the GCE in Chinese international schools and pointed out that GCE was more like an imagined ideal than a realistic template.…”
Section: Focusing On Chinese Context During the Covid-19 Pandemicmentioning
confidence: 99%